Vaginal Carriage of Chlamydia Trachomatis and Other Sexually Transmissible Pathogens Among Adolescents in Nigeria - Felix Emele Emele; Nneka Regina Agbakoba; Chiamaka Princewill Chukwuka; Charlotte Oguejiofor (Medical Network, 2019)
Objectives: Chlamydia trachomatis remains a major cause of genital tract infection and can cause undesirable consequences, such as female infertility. Adolescent girls are physiologically more vulnerable to genital tract infection than older women and need regular screening for genital pathogens. We, therefore, saw the need to screen teenage high school girls in the Anambra State of Nigeria for Chlamydia trachomatis and other potential urogenital pathogens. Study design: This was a Cross sectional study involving 100 randomly selected high school girls, aged 13-18 years, who consented to the study. High vaginal swab samples were collected from the subjects and were analyzed microbiologically; genomic DNA was extracted from each specimen and subjected to PCR analysis. Semi-structured, pre-tested, questionnaires were used to collect relevant bio-data from the participants. The results were analyzed using Chi-square test and percentages. Results: Of the 100 girls, 47(47%) harbored sexually transmissible pathogens in the vagina. Overall, sixty five different kinds of potential urogenital pathogens were recovered, some in co-infection. Organisms represented were as follows: Chlamydia trachomatis, 4(4%); genital Mycoplasmas, 10(10%); Ureaplasmas, 10(10%); Gardnerella vaginalis, 10(10%); and Candida 31(31%). Majority of the girls sought medical treatment from sources other than the hospitals (X2 = 75.9017; p< 0.05). Conclusion: Results showed that sexually transmitted pathogens were common in the high school girls, and alerts of the need for regular vaginal screening and proper medical enlightenment of the adolescents.